Assessing the Assessment : A Critical Look At the June 2003 Assessment of the United Kingdom's Five Tests for Euro Entry - Cottarelli, Carlo (IMF Working Papers; Working Paper, 2004)
This paper provides a framework for evaluating the decision to enter a currency area, including the best timing for entry, and uses it to evaluate the assessment of the five tests for euro entry published by the U.K. Treasury in June 2003. The breadth and depth of its assessment is impressive by any standard. Nonetheless, this paper points at some areas that deserve to be explored further in future assessments. Covering these areas would not necessarily have changed the assessment's conclusion, namely that the case for entry is not yet "clear and unambiguous,." but it would have strengthened any conclusion reached. In addition, the paper highlights that in several areas relevant to the entry decision, the margin for uncertainty will remain significant, regardless of any reasonable attempt to reduce it.